Volleyball Game Analysis Using Computer Vision Algorithms - Plankelj, Marko; Mlakar, Uroš (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
In recent years, modern technologies have made sports more ac-cessible to a wider audience by providing interactive data during broadcasts, reducing the risk of human error, and enhancing ath-letes’ performance through real-time analysis and targeted training insights. This paper combines theoretical and practical approaches by developing an application based on specific convolutional neu-ral networks for volleyball court detection and ball tracking. The results demonstrate the potential of advanced video analytics in sports, allowing users to explore the opportunities of modern tech-nology in improving sports performance.